Efektifitas Pelatihan English Basic Conversation For Hotel Staff Terhadap Self Efficacy Karyawan Hotel Di Palembang - Leovani, Ega (Prosiding University Research Colloquium, 2018)
The research aims to investigate the effectiveness of English basicconversation for hotel staff training on the self-efficacy of hotelemployees in Palembang. The background of this research is that thecity of Palembang will be hosting international events such as ASIANGAMES 2018, and the readiness of the people of Palembang in facingthe MEA especially in the hotel business. Individual factors thatinfluence self-efficacy are job involvement, organizational commitmentand work environment. The data collection of this study usedquestionnaire method and sampling technique, that is, purposivesampling method. The selection of the intended sample is conductedbecause the researcher understands that the required information canbe obtained from a particular group that is able to provide the desiredinformation because they do have such information and they meet thecriteria determined by the researcher. The method of analysis in thisstudy used simple linear regression by performing the classicalassumption test as a condition in performing regression test. The resultof the research demonstrates that the training of English basicconversation for hotel staff has a positive and significant influence onthe self-efficacy of star hotel employees in Palembang.